The Influence of Security, Convenience, and Customer Trust on Purchase Decision in Tokopedia Marketplace in Surabaya City - Muhammad Ricky Setiawan; Hery Pudjoprastyono; Nanik Hariyana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
As one of Indonesia’s largest marketplaces, Tokopedia provides a compelling case study to examine the profound impact of security, convenience, and consumer trust on purchasing decisions in the rapidly evolving digital commerce. However, the extent to which these factors influence purchasing decision remains a critical issue. This research is designed to analyze the impact of security, convenience, and customer trust on purchasing decision in the Tokopedia marketplace. A quantitative and descriptive framework was applied using purposive sampling, involving 102 respondents who are Tokopedia users in Surabaya city, aged 17 years and above, who have made transactions within the past year. Primary data were collected through questionnaires, while secondary data were acquired from academic references. Data processing was undertaken via Partial Least Squares-Structural Equation Modeling using SmartPLS. Model evaluation included outer model assessment for construct validity and reliability through Cronbach’s Alpha, Composite Reliability, and Average Variance Extracted (AVE), as well as inner model evaluation using R-square, Q-square, and bootstrapping tests. The results show that security, convenience, and customer trust is positive & significantly influence purchasing decision. Convenience has the most substantial effect, highlighting the importance of accessible and intuitive navigation. Customer trust is strengthened by seller integrity and transparency, while security is enhanced by cash-on-delivery (COD) systems. This study contributes to the TAM Theory (technology acceptance model) and TRA Theory (theory of reasoned action), reinforcing that security, convenience, and customer trust are crucial determinants in online purchasing decision.